Thanh niên Việt Nam : (UNFPA Vietnam, 2011)
Young people who enter the labour force equipped with appropriate skills can refresh and improve the quality of their country's human capital. Young people are perhaps the most critical determinant of long-term growth and development. For the purpose of this profile, the youth demographic is defined as the age group between 15-24 years. This booklet is the eighth in a series published by the United Nations Population Fund (UNFPA) during recent years. Information is drawn from the Viet Nam 2009 Population and Housing Census data and from the Major Findings, a series of census data monographs developed by the General Statistics Office (GSO) and the UNFPA. The aim of this booklet is to analyse the Census data and create a profile of indicators highlighting trends among the young population as the generation most vital to Viet Nam’s future development.